Talking Chips Media for Developing The Group Dynamics in Guidance and Counseling-Grouped - Silalahi, Esrawati; Hartini, Sri; Prabowo, Agung Budi; Siswanti, Rini (Universitas Islam Negeri Raden Intan Lampung, 2022)
Learning media is an inseparable part of learning activities. In addition to being needed when delivering lessons, the media is even needed in the implementation of guidance and counseling services so that the intentions in these activities can be conveyed properly to students. The purpose of this study is to clarify the use of media that is often used to practice speaking skills, speaking chips, as a solution to develop group dynamics in group guidance and counseling services. The existence of group dynamics is one indicator of success in group guidance and counseling services. The research method used is library research, which is carried out by interpreting several data sources such as books and journals or relevant scientific articles. The result of this research is that speaking chips media can be used to encourage students to actively communicate and interact in groups so that the dynamics of group guidance and counseling services develops. In contrast to previous studies that discussed techniques and methods in group guidance and counseling services, this research focuses on developing group dynamics as an important part of group services